2022
DOI: 10.3390/mi13030357
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Blood Viscosity According to the Hematocrit and the Shear Rate

Abstract: The rheological properties of blood depend highly on the properties of its red blood cells: concentration, membrane elasticity, and aggregation. These properties affect the viscosity of blood as well as its shear thinning behavior. Using an experimental analysis of the interface advancement of blood in a microchannel, we determine the viscosity of different samples of blood. In this work, we present two methods that successfully normalize the viscosity of blood for a single and for different donors, first acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
6
1
Order By: Relevance
“…As the respective error bars overlapped in the shear rate range of 10 0 -10 3 1/s, we concluded that the presence of RBCs after centrifugation did not exert any effect on the shear viscosity of follicular fluids. Generally, in whole blood, shear viscosity increases with increasing concentration of RBCs in the plasma (low-viscosity Newtonian fluids) [32]. However, this effect was negligible in this study, indicating that the concentration of RBCs in follicular fluids was visibly minute.…”
Section: Shear Viscosity Of Follicular Fluidscontrasting
confidence: 53%
“…As the respective error bars overlapped in the shear rate range of 10 0 -10 3 1/s, we concluded that the presence of RBCs after centrifugation did not exert any effect on the shear viscosity of follicular fluids. Generally, in whole blood, shear viscosity increases with increasing concentration of RBCs in the plasma (low-viscosity Newtonian fluids) [32]. However, this effect was negligible in this study, indicating that the concentration of RBCs in follicular fluids was visibly minute.…”
Section: Shear Viscosity Of Follicular Fluidscontrasting
confidence: 53%
“…Viscous losses result in the absorption of ultrasonic energy directly affecting the attenuation, as it is clear from relation 3, is reported to increase as a storage lesion and was linked to a series of structural and biochemical alterations [36]. The rheological properties of blood, which have been demonstrated to follow a non-Newtonian behavior [37], where the viscosity increases with decreased shear rates [38], high spatial shear strain rates would be essential for a capillary flow rate for blood preserved more than three weeks. The modifications that occur, including the increased cellular buoyancy in blood drawn for donation as storage lesions [39] and increased aggregation [36], can also contribute to the attenuation.…”
Section: Resultsmentioning
confidence: 99%
“…Hematocrit also participates in the hemodynamic interactions inside blood capillaries (Boal, 2001;Spann et al, 2016;Bouchnita et al, 2021). Known to fluctuate from one patient to another, hematocrit can reach 45% and can significantly modify the rheological properties of blood, including its viscosity and cellular interactions (Nader et al, 2019;Trejo-soto and Hernández-machado, 2022). In fact, the impact of hematocrit is particularly clear from a micro-rheological point of view: when analysing the in vivo distribution of RBCs, it was observed that the vascular network, and more specifically the subsequent and smallest generations, experience a heterogeneous distribution of hematocrit as a consequence of successive microvascular bifurcations and uneven velocity distributions (Chien et al, 1985;Fenton et al, 1985;Pries et al, 1989).…”
Section: Figurementioning
confidence: 99%